2021
DOI: 10.1002/aoc.6371
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired cobalt molecular electrocatalyst for water oxidation coupled with carbon dioxide reduction

Abstract: To mimic photosynthesis in green plants, it is a crucial challenge to drive water oxidation and CO 2 reduction in one single system. In this study, we present a bioinspired trinuclear pyridinedicarboxylate cobalt complex (Et 3 NH) 2 [Co III 2 Co II (OH 2 )(pda) 5 ]ÁH 2 O (1) that is capable of homogeneously electrocatalytic water oxidation and CO 2 reduction simultaneously. The designed mix-valent cobalt complex is in a V-configuration composed of two terminal Co III ions and one central Co II ion coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 88 publications
(103 reference statements)
1
7
0
Order By: Relevance
“…Complexes 1 and 2 are the first two compounds coordinated with Schiff base ligand for both water oxidation and CO 2 reduction. The complexes 1 and 2 show the electrocatalytic activity for water oxidation with TOFs of 3.66 s −1 and 7.88 s −1 with the overpotentials of 728 mV and 216 mV, meanwhile the catalytic reduction of CO 2 to CO with the TOF values of 0.38 s −1 at −1.65 V and 15.97 s −1 at −1.60 V, respectively, which are higher than or comparable with those of reported complexes ( Table S2 ) [ 31 , 32 , 33 , 34 ]. Through great efforts, we used the same Schiff base ligand L to obtain mononuclear Mn III complex 1 and hetero-binuclear Mn II –Cu II complex 2 for accurately comparing their catalytic behaviors.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Complexes 1 and 2 are the first two compounds coordinated with Schiff base ligand for both water oxidation and CO 2 reduction. The complexes 1 and 2 show the electrocatalytic activity for water oxidation with TOFs of 3.66 s −1 and 7.88 s −1 with the overpotentials of 728 mV and 216 mV, meanwhile the catalytic reduction of CO 2 to CO with the TOF values of 0.38 s −1 at −1.65 V and 15.97 s −1 at −1.60 V, respectively, which are higher than or comparable with those of reported complexes ( Table S2 ) [ 31 , 32 , 33 , 34 ]. Through great efforts, we used the same Schiff base ligand L to obtain mononuclear Mn III complex 1 and hetero-binuclear Mn II –Cu II complex 2 for accurately comparing their catalytic behaviors.…”
Section: Introductionsupporting
confidence: 58%
“…In 2021, Wang’s group developed a mononuclear copper complex [Cu II L 1 2 ](ClO 4 ) 2 ·2CH 3 OH ( L 1 = methoxy-di-pyridin-2-ylmethanol) as a bifunctional electrochemical catalyst for CO 2 reduction and water oxidation, of which the turnover frequencies (TOFs) were 2.99 s −1 and 9.20 s −1 , respectively [ 33 ]. Later, they reported a multinuclear cobalt complex (Et 3 NH) 2 [Co III 2 Co II (OH 2 )(pda) 5 ] (H 2 pda = 2,6-pyridinedicarboxylic acid) as an excellent homogeneous electrochemical catalyst for water oxidation and CO 2 reduction, where the labile aqua ligand played an important role in improving the catalytic performance [ 34 ]. Except for the above works, most of the coordination complexes and other materials in this area are heterogeneous catalysts [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…S21 †), affording faradaic efficiencies of 96% and 97%, respectively, which are comparable with those of previously reported homogeneous cobalt-based WOCs. [37][38][39][40] The difference in the amount of oxygen production indicates that the catalytic activity of complex 2 is much lower than that of complex 1.…”
Section: Electrochemical Testsmentioning
confidence: 99%
“…[31][32][33][34][35][36][37] Nonetheless, they are less used for homogeneous electrochemical water oxidation. [38][39][40][41] It was reported that nanoparticles of cobalt oxides or cobalt hydroxides generated during the synthesis of cobalt complexes are also catalytically active for water oxidation, causing confusion regarding the interpretation of the intrinsic properties of the as-synthesized cobalt complexes. 42,43 In this work, we report the synthesis, electrochemical characterization, and electrocatalytic properties of a mononuclear cobalt complex [Co(N3Py2)(H 2 O)](ClO 4 ) 2 (1) of high purity (N3Py2 = 2,5,8-trimethyl-1,9-bis(2-pyridyl)-2,5,8-triazanonane) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…31–37 Nonetheless, they are less used for homogeneous electrochemical water oxidation. 38–41 It was reported that nanoparticles of cobalt oxides or cobalt hydroxides generated during the synthesis of cobalt complexes are also catalytically active for water oxidation, causing confusion regarding the interpretation of the intrinsic properties of the as-synthesized cobalt complexes. 42,43…”
Section: Introductionmentioning
confidence: 99%